'… if U equals U what does the second U mean?': sexual minority men's accounts of HIV undetectability and untransmittable scepticism. Issue 9 (1st September 2021) - Grace, Daniel; Nath, Ronita; Parry, Robin; Connell, James; Wong, Jason; Grennan, Troy
Abstract: The everyday meaning and use of HIV 'undetectability' raises significant questions about the social and sexual significance of this state of viral suppression. We conducted in-depth, semi-structured interviews with 25 sexual minority men living in Vancouver, Canada, including men living with HIV. Interviews were audio-recorded, transcribed verbatim and analysed using grounded theory. Most participants understood being undetectable to signify that someone living with HIV is at a 'low, ' 'lower, ' or 'slim to no' risk of sexually transmitting HIV, as opposed to meaning 'uninfectious' or 'untransmittable'. Men discussed how undetectability was communicated in-person and online, including via sexual networking apps, and revealed how it is sometimes confused or conflated with another biomedical advance in HIV-prevention, namely pre-exposure prophylaxis (PrEP). HIV-negative men expressed significant scientific scepticism, a reluctance to incorporate a partner's low viral load or undetectable HIV status into their sexual decision-making, and an enduring fear associated with knowingly having sex with someone who is HIV-positive. We describe this as a form of untransmittable scepticism . While international campaigns have worked to communicate the scientific message that 'undetectable equals untransmittable' (U = U), the sexual stigma attached to HIV remains durable among some gay, bisexual, queer and other men who have sex with men.